Alkali and Silane Treated Ramie Yarn Fiber for 3D-Printed Filament Composite Material Reinforcement - Lilis Safitri; Sutikno Sutikno; Putu Suwarta (Engineering Proceedings, 2025)
Natural fiber such as ramie is a type of reinforcement material derived from natural sources. These reinforcement materials offer an environmentally sustainable solution contributing to eco-friendly practices. However, natural fibers face challenges as reinforcement materials due to the presence of non-cellulosic impurities and structural irregularities, which reduce crystallinity. This study explores the impact of alkali using sodium hydroxide (NaOH 5%) and silane using 3-(Aminopropyl) trimethoxy silane (APTES 1% and 3%) treatments on the chemical structure and crystallinity index of ramie yarn fiber (Boehmeria nivea). Alkali treatment effectively removes non-cellulosic impurities, resulting in an improved crystalline structure, while silane treatment modifies the fiber surface, introducing functional groups that alter its chemical structure. The chemical modifications were analyzed by using Fourier transform infrared spectroscopy (FTIR), and the crystallinity index was measured through X-ray diffraction (XRD). The findings revealed that alkali treatment significantly increased the crystallinity index (Crl) of ramie fibers to the highest value of 82.63%, and silane treatment primarily enhanced surface reactivity, facilitating better adhesion and chemical bonding with the matrix. This research highlights the potential of alkali and silane treatments for optimizing ramie fiber for use in advanced polymer composite applications.